Psychological Impacts on Post-COVID-19 Patients in Raptisonari Rural Municipality, Banke District - Lal Mani Acharya (Britain International of Exact Sciences (BIoEx) Journal, 2024)
This study investigates the psychological effects experienced by patients who have recovered from COVID-19 in the Raptisonari Rural Municipality of Banke District. The primary objective is to elucidate the actual psychological impacts on these individuals. The research adopts a descriptive methodology, encompassing both quantitative and qualitative data. A sample of 80 respondents, all above the age of 20, was selected using snowball sampling. Data collection was conducted through questionnaires and informal interviews during direct visits to the respondents. The collected primary data were meticulously edited and presented in the final report, with tabulation aligned to the study's objectives. Data entry and analysis were performed using Microsoft Excel, enabling the creation of relevant tables and diagrams. The analysis revealed that 40% of respondents were aged 25-29, while only 1.25% were in the 55-59 age group. Additionally, 72.5% of the respondents belonged to the Janajati community, and all respondents were literate, with 26.25% having completed the SLC/SEE. Employment status showed that 55% of respondents were job holders. In terms of religious affiliation, 87.5% were Hindu. Regarding symptoms, 85% reported experiencing fever, cough, and tiredness, with eight clients specifically mentioning fever and four mentioning cough. Preventive measures identified included mask-wearing, as reported by 39 clients, and 35% of clients were diagnosed with COVID-19 at hospitals. The psychological impact of the COVID-19 diagnosis was significant, with 68.75% of respondents expressing fear upon diagnosis. During the isolation period, 83.75% of the respondents were in home isolation, with 50% fearing death and 45% expressing happiness upon discharge from isolation. Post-recovery, 66.25% of the respondents received congratulations from friends and family upon meeting them. This study highlights the profound psychological effects on COVID-19 recovered patients and underscores the need for targeted mental health support for this population.